2009
DOI: 10.1007/s10714-009-0880-0
|View full text |Cite
|
Sign up to set email alerts
|

Emergent universe scenario in the Einstein–Gauss–Bonnet gravity with dilaton

Abstract: We obtain cosmological solutions which admit emergent universe (EU) scenario in the framework of Einstein Gauss-Bonnet gravity coupled with a dilaton field in four dimensions. The coupling parameter of the Gauss-Bonnet terms and the dilaton in the theory are determined for obtaining an EU scenario. The corresponding dilaton potential which admits such scenario is determined. It is found that the GaussBonnet (GB) terms coupled with a dilaton field plays an important role in describing the dynamics of the evolut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 105 publications
(102 reference statements)
0
45
1
Order By: Relevance
“…Another possibility for the Emergent Universe scenario is to consider models in which the scale factor asymptotically tends to a constant in the past [14,15,[25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility for the Emergent Universe scenario is to consider models in which the scale factor asymptotically tends to a constant in the past [14,15,[25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…it admits black-hole solutions [47][48][49][50][51] and gives rise to cosmic inflation at the early epoch [52]. Late-time accelerated expansion of the universe is particularly a very special feature of such an action [52][53][54][55][56][57]. Moreover, important issues like late-time dominance of dark energy after a scaling matter era, thus alleviating the coincidence problem crossing the phantom divide line, and compatibility with the observed spectrum of cosmic background radiation have also been addressed recently [58][59][60][61].…”
Section: Introductionmentioning
confidence: 99%
“…EU scenario has been explored with quintom matter [16] and further investigated the realization of the scenario with a non-conventional fermion field to obtain a scale invariant perturbation [17]. It has been shown that the EU scenario can be implemented successfully in the framework of general relativity [13] in addition to Gauss-Bonnet gravity [18]. The modified Gauss-Bonnet gravity as gravitational alternative for dark energy is however considered by Nojiri and Oddintsov [19].…”
Section: Introductionmentioning
confidence: 99%